Indonesia`s Palm Oil Industrialization: The Resistance of Tanjung Pusaka Villagers, Central Kalimantan Against Palm Oil Industry - Wulansari, Ica (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2017)
ABSTRACTIndonesia`s Palm oil industry is the greatest export commodity in the world. Palm oil industry has been developed since Soeharto`s administration with World Bank`s initiative. Indonesia`s development pattern is modernization which is fully supported by global capitalist agent. Furthermore, the government of Indonesia has issued policies to support this industry and the ease of accessibilty for investor to build in Indonesia. Most of the policies focus on economic interest with lack of attention to social and environmental issues. The paper applies qualitative method to analyze through literature studies and depth interview. As a result, the writer attempt to discuss the relationship of various concepts and theories regards to Resistency, Modernization and The Modern World-System theory. In fact, Indonesia as palm oil producer do not have bargaining power to determine the price due to global politic has structured to limit profit. Meanwhile, Central Kalimantan has the negative impact of environment and society that caused by palm oil industry. Tanjung Pusaka villagers refuse their region to be transform as palm plantation because they believe that their life is better now that being part of plantation. The purpose of this paper is to explain how villagers have capability of resistance for the sake of social life and environmental preservation.Keywords: Palm, Indonesia, industry, policies, Central KalimantanABSTRAKIndustri minyak sawit Indonesia merupakan komoditas ekspor terbesar di dunia saat ini. Industri minyak sawit telah dibangun sejak kepemimpinan Soeharto yang didukung oleh Bank Dunia. Pola pembangunan Indonesia adalah modernisasi yang disokong oleh agen kapitalis global. Lebih lanjut, Pemerintah Indonesia telah mengeluarkan kebijakan untuk mendukung industri minyak sawit dan memberikan kemudahan bagi investor untuk berinvestasi di sektor ini. Kebijakan-kebijakan tersebut hanya fokus terhadap kepentingan ekonomi dan minimnya perhatian terhadap isu sosial dan lingkungan hidup. Tulisan ini menggunakan metode kualitatif untuk menganalisa melalui studi literatur dan wawancara mendalam. Hasilnya, penulis berusaha mendiskusikan hubungan antara beragam konsep dan teori mengenai Resistensi, Modernisasi dan Teori Sistem Dunia. Faktanya, Indonesia sebagai produsen minyak sawit tidak memiliki kekuatan untuk menentukan harga karena politik global yang telah dibentuk untuk membatasi keuntungan yang didapatkan. Sementara itu, provinsi Kalimantan Tengah mengalami dampak negatif terhadap lingkungan hidup dan sosial yang disebabkan oleh industri minyak sawit. Warga Dusun Tanjung Pusaka menolak wilayahnya dijadikan perkebunan sawit karena mereka yakin hidupnya akan lebih baik dibandingkan menjadi bagian dari perkebunan sawit. Tujuan penulisan ini paper ini untuk menjelaskan bagaimana masyarakat desa mampu melakukan upaya resistensi demi kepentingan sosial dan pelestarian lingkungan hidup.Kata kunci: Sawit, Indonesia, industri, kebijakan, Kalimantan Tengah